A brief review on the utilization of biopolymers in the manufacturing of natural fiber composites - Cionita, Tezara; Jamiluddin, Jaafar; Wong, Ling-Shing; Siregar, Januar Parlaungan; Al Emran, Ismail; Mohamad Farid, Sies; Irawan, Agustinus Purna; Hadi, Agung Efriyo; Fitriyana, Deni Fajar; Teuku Rihayat, . (Taylor's University, 2024)
The study briefly reviews the potential of biopolymers such as polylactic acid (PLA) and Polyhydroxyalkanoate (PHA) to become a green matrix in developing entirely biodegradable composites. The suitability of PLA and PHA in the production of entirely biodegradable natural fibre composites is discussed in this paper. The thermal properties investigation reveals that PLA and PHA are compatible with natural fibre for biocomposite fabrication. Furthermore, this study investigates the effect and performance of mechanical properties, predominantly tensile properties of combination between different natural fibres with biopolymers. In Addition, all essential elements affecting the mechanical characteristics of biocomposites are highlighted. Therefore, the current study's findings are expected capable to provide a clear picture of the biopolymer's position in producing biocomposites. It is also expected that the findings from this study will help further improve the performance of natural fibre reinforced biopolymer composites.